Synthesis, Characterization and Staining Ability of Novel Azo Dye Based on Curcumin and Its Au(III) Complex - Wesam Dheyab Kzar; Hasan Shamran Mohammed; Fatimah Swadi Zghair; Zahia Zizi (Universitas Gadjah Mada, 2023)
Azo dye ligand (HMDA), namely N-(4-((E)-((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-3,5-dioxohepta-1,6-dien-4-yl)diazenyl)phenyl)acetamide was prepared by coupling diazonium salt of 4-aminoacetanilide with curcumin in basic conditions. The HMDA ligand and its Au(III) complex were characterized by elemental analysis, mass spectroscopy, 1H-NMR, FTIR, UV-visible spectra, and molar conductivity. The molar ratio method was applied to ascertain the stoichiometric composition of the Au(III) complex in aqueous solution, which was 1:2 (metal ion to ligand). HMDA ligand binding with Au(III) ion used the enolate form moiety of curcumin under alkaline conditions which was observed by infrared spectra and investigated by elemental analysis and 1H-NMR. HMDA and its Au(III) complex have been evaluated as stains for intestine, pancreas and kidney tissues of mice and exhibited important contrast. Both compounds showed the most potent staining activity toward blood cells, collagen, muscle fibers and cytoplasm in the selected tissues of mice. This azo dye and its complex of Au(III) succeeded in dyeing mice tissues, compared with the conventional stains.